2014
DOI: 10.3233/tad-140400
|View full text |Cite
|
Sign up to set email alerts
|

A multiprofessional client-centred guide to implementing assistive technology for clients with cognitive impairments

Abstract: OBJECTIVE: The aim was to develop a framework for prescribing assistive technology (AT) for people with cognitive impairment and provide guidelines for clinical practice. METHODS: A qualitative approach was used to develop and validate the guide. RESULTS: The guide is directed mainly towards occupational therapists and neuropsychologists. It comprises six main steps, 1. Meeting the client, 2. Goal setting, 3. Assessment, 4. Choice of relevant devices, 5. Teaching and training plan, 6. Evaluation and follow-up.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…During assessments and interviews, SOs could provide invaluable knowledge about the PwD's past and current needs as described by Collins [20]. SOs often encouraged the PwDs to both try new time AT and continue to use time AT, which is supported in earlier studies [30,31]. Furthermore, our results showed that it was mostly SOs that provided training and reminders for the PwDs in using time AT.…”
Section: Discussionsupporting
confidence: 78%
“…During assessments and interviews, SOs could provide invaluable knowledge about the PwD's past and current needs as described by Collins [20]. SOs often encouraged the PwDs to both try new time AT and continue to use time AT, which is supported in earlier studies [30,31]. Furthermore, our results showed that it was mostly SOs that provided training and reminders for the PwDs in using time AT.…”
Section: Discussionsupporting
confidence: 78%
“…Rehabilitation resources are more restricted in Sweden for persons with MACI, thus one hypothesis would be that people with MACI receive less external support in acquiring new skills after their brain injury. Also occupational therapists need to improve their skills in training patients to use e-services [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To raise the level of evidence of the effectiveness of eMMDs for medication administration used by people with AD, it is important to define the context of use and evaluate usability in this population (Paterson et al, 2017). In addition, the training strategies must be defined (Bartfai & Boman, 2014). In fact, persons with AD need specific training to learn how and when to use their assistive technology.…”
Section: Use Of An Electronic Pillboxmentioning
confidence: 99%